2008
DOI: 10.1111/j.1365-2966.2008.12868.x
|View full text |Cite
|
Sign up to set email alerts
|

Hα kinematics of the Spitzer Infrared Nearby Galaxies Survey – II

Abstract: This is the second part of an Hα kinematics follow‐up survey of the Spitzer Infrared Nearby Galaxies Survey (SINGS) sample. The aim of this paper is to shed new light on the role of baryons and their kinematics and on the dark/luminous matter relation in the star‐forming regions of galaxies, in relation with studies at other wavelengths. The data for 37 galaxies are presented. The observations were made using Fabry–Perot interferometry with the photon‐counting camera FaNTOmM on four different telescopes, namel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
77
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 118 publications
11
77
0
Order By: Relevance
“…High-redshift galaxies are clumpier and show more irregular structures than local galaxies, further complicating the visual characterization of mergers (Elmegreen et al 2007). Kinematic classifications assume that isolated disks exhibit smooth velocity gradients whereas mergers show more asymmetric and chaotic kinematic features (Shapiro et al 2008;Dicaire et al 2008;Colina et al 2005). However, this assumption does not consider post-coalescence mergers which may also display disk-like kinematics (Bellocchi et al 2012).…”
Section: Star Formation Rate Stellar and Dynamic Massmentioning
confidence: 99%
“…High-redshift galaxies are clumpier and show more irregular structures than local galaxies, further complicating the visual characterization of mergers (Elmegreen et al 2007). Kinematic classifications assume that isolated disks exhibit smooth velocity gradients whereas mergers show more asymmetric and chaotic kinematic features (Shapiro et al 2008;Dicaire et al 2008;Colina et al 2005). However, this assumption does not consider post-coalescence mergers which may also display disk-like kinematics (Bellocchi et al 2012).…”
Section: Star Formation Rate Stellar and Dynamic Massmentioning
confidence: 99%
“…These authors also showed that the inner slope of the rotation curve of NGC 2976 is likely affected by the barlike perturbation. Numerical simulations of barred disks arrived at a similar conclusion about the impact of the bar on the inner shape of rotation curves (Valenzuela et al 2007;Dicaire et al 2008). Randriamampandry et al (2015) performed numerical simulations to determine a corrected rotation curve for another barred galaxy (NGC 3319), free from the perturbing motions induced by the bar.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral lines from stars, neutral gas, molecular gas, and ionized gas of nearby galaxies (e.g., de Zeeuw et al 2002;Helfer et al 2003;Dicaire et al 2008;Walter et al 2008) trace galaxy dynamics out to different radii (e.g., Yun et al 1994;Aalto et al 1999), and in some cases they may reveal the evolution and interaction history of galaxies (Davis et al 2011). Emission lines from molecular gas and ionized gas are the most common tracers for a large sample of resolved galaxy kinematics out to z∼3 (e.g., Tacconi et al 2006;Förster Schreiber et al 2009;Daddi et al 2010;Gnerucci et al 2011), for which the gas traces the star-forming fuel and massive star forming regions.…”
Section: Introductionmentioning
confidence: 99%